Volume of Text in the Context of Stylistic Organization of Narration (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The analysis of the text’s style cannot be fruitful or convincing enough without establishing its relevant specific elements. The volume of a speech work is an essential feature of the text type. The strictness of narration determines the entire stylistic system of a short-text narrative. This problem cannot be solved without the active involvement of linguo-stylistics. When analyzing the semantic coherence of a novella’s text, it is necessary to primarily use the structural-compositional and linguistic components of this text type.